(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines various aspects of vehicle braking, especially in the context of experimental studies. Describes the moving braking system and methods for improving its effectiveness, including accelerator and secant braking. The influence of environmental factors on the risk of pregnancy, analysis of quantitative calculations and the functioning of the experiment are also discussed. Various braking methods are considered, including the use of an engine as an assistant and dynamic braking mechanisms. Formulas and expressions describing the processes of braking of cars are presented, and the influence of prolonged braking on automobile safety is also considered. The study also addresses the issues of self-paced education in the field of transport safety and the risks associated with insufficient braking.